Respuestas

2012-06-28T19:42:01+02:00

comensemos:

 

Cos2x+Cos4x=0  


sabemos:

 

cos(4x) = 2 cos^2(2x) - 1


por tanto:


ccos(2x) + 2 cos^2(2x) - 1=0


2 cos^2(2x) + cos(2x) - 1 =0

    2cos(2x)                 -1     ----> aspa simple

     cos(2x)                 +1    

 

(2cos(2x)-1)(cos(2x)+1)=0

 

2cos(2x)-1=0      cos(2x)+1=0

cos(2x)=1/2       cos(2x)=-1 

 

si x esta entre 0 y 360

 

toma los valores:


cos(60)=1/2 , cos(300)=1/2  ,  cos(180)=-1


x=30 , x=150 , x=90

________________________

Cos4x-cos6x=0

 

cos(4x)=cos(6x)

 

4x=6x=0

 

x=0

 

un gusto....=D